Primary-Secondary Wavelengths Spectrophotometric Determination of Trace Amounts of Cadmium with 2,4-Dibromo-6-Carboxy-Benzenediazoaminoazobenzene - Li, Mei; Gao, Hong-Wen; Shi, Shu-Ren; Li, Yu-Cheng (Asian Journal of Chemistry, 2010)
In basic solution and in the- presence of non-ionic surfactant, emulsifier OP, the reaction of cadmium (Cd2+) with new chromogenic agent, 2,4-dibromo-6-carboxy-benzenediazoaminoazobenzene (DBCBAA) forms red complex. It is one of most sensitive determinations of trace cadmium in environment. Because of the interference of excess of DBCBAA on complex absorbance the new method, primary-secondary wavelengths spectrophotometry (PSWS), was applied for the determination of trace amounts of cadmium in wastewater. The results showed that the working wavelengths should be selected at 520 and 610 nm and such a method gives out the higher precision, accuracy and lower detection limit than by ordinary spectrophotometry. By testing several wastewater samples, the relative standard deviations were less than 7.2% and the recovery rate of Cd is between 90 and 108%.